Economic Impact of Selected Conflicts in the Middle East : What Can We Learn from the Past? - Sab, Randa (IMF Working Papers; Working Paper ;, 2014)
Using narrative-based country-case studies, war episodes in the Middle East were examined to assess their economic impact on conflict and neighboring economies. The paper found that conflicts led to a contraction in growth, higher inflation, large fiscal and current account deficits, loss of reserves, and a weakened financial system. Post-conflict recovery depended on the economic and institutional development of the country, economic structure, duration of the war, international engagement, and prevailing security conditions. The net economic impact on neighboring countries varied according to their initial economic conditions, number and income level of refugees they hosted, economic integration, and external assistance.